Clinical significance of tumor mitotic rate and lack of epidermal attachment in melanoma of the head and neck. Issue 8 (22nd March 2018) - Babajanian, Eric E.; Tamaki, Akina; Bordeaux, Jeremy S.; Honda, Kord; Zender, Chad A.
Abstract: Background: The primary purpose of this study was to identify the prognostic role of primary dermal melanoma and tumor mitotic rate in melanomas of the head and neck. Methods: A retrospective review of the histopathologic, clinical, and demographic data of 256 patients was performed to investigate the impact of primary dermal melanoma and tumor mitotic rate on sentinel lymph node positivity, recurrence, and 5‐year overall and disease‐free survival. Results: Increased tumor mitotic rate, but not primary dermal melanoma, is a significant predictor of sentinel lymph node positivity and higher likelihood of recurrence. Survival analysis demonstrated that both increased tumor mitotic rate and primary dermal melanoma decreased the 5‐year overall and disease‐free survival rates of patients with head and neck melanoma lesions. Conclusion: Tumor mitotic rate and primary dermal melanoma may have prognostic significance for both overall and disease‐free survival in patients with head and neck melanoma. A larger prospective study is warranted to further elucidate prognostic factors for melanoma in the head and neck region.